Rethinking Orientalism of Muslims in Ayaan Hirsi Ali’s Infidel - Sadiya Abubakar Isa; Md Salleh Yaapar; Suzana Haji Muhammad (Indonesian Journal of Islam and Muslim Societies, 2019)
Edward Said’s Orientalism questions the Western representation of the Eastern ‘other’, especially the Arab Muslims. A misrepresentation that has always treated the orient with inferiority; as barbaric and backward compared to the refined, reasoning and advanced Occident. This form of representation is what Ayaan Hirsi Ali embarked on in her bestselling memoir Infidel (2007). It chronicles her geographical journey from Somalia to Saudi Arabia, Ethiopia, Kenya and the Netherlands, and her flight from Islam to Atheism. A belief system she finds more appealing to reasoning than Islam which is (according to her) backward and barbaric. Her steadfast criticism of Islam is vividly reflected in her memoir, which ascribes the oppression and tribulations of women to Islam, irrespective of geographical or cultural influence. Such claims are tantamount to feminist Orientalism of Muslim women, whose claims of liberating Muslim women and rescuing them from the oppressive Islam cannot be overemphasized. This paper argues that the practices of misogyny are rooted in culture and not Islam. Thus, it investigates three main points which are central to the ‘Islam oppresses women’ debate: Female Genital Mutilation, Early and/or Forced Marriage and Women as sex objects. Edward Said’s Culture and Imperialism as a continuation of Orientalism, propose solutions to the identified problems in Orientalism, which is to unread the misrepresentations by identifying submerged details. Through a contrapuntal reading of Infidel (2007), this study counter-narrates the distortion of Islam by drawing upon authentic Islamic sources. Karya Edward Said Orientalisme mempertanyakan representasi Barat dari “yang lain” di Timur, terutama Muslim Arab. Sebuah penyajian yang keliru yang selalu memperlakukan “orient” dengan inferioritas, sebagai biadab dan terbelakang dibandingkan dengan “Occident”, penalaran dan kemajuan Barat. Bentuk representasi inilah yang memulai Ayaan Hirsi Ali dalam memoarnya yang terlaris, iInfidel (2007). Ini mencatat perjalanan geografisnya dari Somalia ke Arab Saudi, Ethiopia, Kenya, dan Belanda, dan pelariannya dari Islam ke Ateisme. Sebuah sistem kepercayaan yang ia temukan lebih menarik untuk dipertimbangkan daripada Islam yang (menurutnya) terbelakang dan biadab. Kritiknya yang teguh terhadap Islam tercermin dengan jelas dalam memoarnya, yang mengaitkan penindasan dan kesengsaraan wanita dengan Islam, terlepas dari pengaruh geografis atau budaya. Klaim semacam itu sama dengan Orientalisme feminis perempuan Muslim, yang klaimnya membebaskan perempuan Muslim dan menyelamatkan mereka dari Islam yang menindas tidak bisa terlalu ditekankan. Makalah ini berpendapat bahwa praktik misogini berakar pada budaya dan bukan Islam. Oleh karena itu, laporan ini menyelidiki tiga poin utama yang menjadi pusat perdebatan “Islam menindas wanita”: Mutilasi Alat Kelamin Wanita, Pernikahan Dini dan/atau Paksa dan Wanita sebagai objek seks. Karya Edward Said Culture and Imperialism sebagai kelanjutan dari Orientalisme, mengusulkan solusi untuk masalahmasalah yang diidentifikasi dalam Orientalisme, yakni untuk membaca kesalahan representasi dengan mengidentifikasi detail yang terendam. Melalui pembacaan kontrapuntal dari Infidel (2007), penelitian ini membaut kontra-narasi atas distorsi Islam dengan memanfaatkan sumbersumber Islam otentik.